Developing Children's Concepts in Mathematics and Natural Sciences in Elementary School: From Initial Representations to Scientific Concepts - Isaev E.I; Margolis A.A; Safronova M.A (Moscow State University of Psychology and Education, 2022)
The article provides psychological and pedagogical background for a technique aimed at transforming children's initial representations in mathematics and natural sciences into scientific concepts in elementary school. The methodological basis underlying this technique is largely shaped by L.S.Vygotsky's ideas of holistic and unified development of concepts in the process of learning. We emphasize the key ideas of designing tools for working with students' initial representations and transforming them into mathematical and natural scientific concepts: identification and joint discussion of children's naive representations, reflective assessment of different views on the explored subject concept, coordination of opinions and assessments. We analyze the main approaches and practices of working with the students' initial representations developed in foreign and Russian psychological and pedagogical research. It is worth noting that there is no universally recognized technique for transforming students' initial representations into scientific concepts in elementary school; nonetheless, there is a number of effective methods in pedagogical practice that we outline in the paper. Finally, we stress the importance of training teachers to work with children's initial representations in the course of developing their scientific concepts within the learned subject.